The K‐theory of toric varieties in positive characteristic. (7th August 2013) - Cortiñas, G.; Haesemeyer, C.; Walker, Mark E.; Weibel, C.
Abstract : We show that if X is a toric scheme over a regular ring containing a field of finite characteristic, then the direct limit of the K ‐groups of X taken over any infinite sequence of non‐trivial dilations is homotopy invariant. This theorem was known in characteristic 0. The affine case of our result was conjectured by Gubeladze.